High regional variability of HIV, HCV and injecting risks among people who inject drugs in Poland: comparing a cross-sectional bio-behavioural study with case-based surveillance - Rosińska, Magdalena (BMC Infect Dis, 2015)
BACKGROUND: People who inject drugs (PWID) are an important group at risk of blood borne infections in Poland. However, robust evidence regarding the magnitude of the problem and geographical variation is lacking, while coverage of prevention remains low. We assessed the potential of combining bio-behavioural studies and case-based surveillance of PWID to gain insight into preventive needs in Poland. METHODS: Results of a bio-behavioural human immunodeficiency virus (HIV) and hepatitis C virus (HCV) prevalence study among ever injectors in six regions in Poland were compared with HIV case-based surveillance trends from 2000 to 2012. Logistic regression was used for multivariable analyses in the prevalence study. The case surveillance data were correlated with prevalence data, by region, to determine surveillance validity and identify any recent trends. RESULTS: HIV seroprevalence (18% overall) differed more than ten-fold across regions (2.4% to 32%), but HCV seroprevalence and the proportion of PWID sharing needles/syringes in the past 12 months were similar, 44% to 68% and 22% to 29%, respectively. In multivariable models accounting for socio-demographic factors, duration of injecting history and needle sharing practices, regional differences were significant for both HIV and HCV seroprevalence with adjusted odds ratios varying up to a factor of 12.6 for HIV and 3.8 for HCV. The number of new cases of HIV diagnosed in each region during the bio-behavioural study period was strongly correlated (r = 0.93) with HIV prevalence. There was an overall decreasing trend in the number of new diagnoses of HIV over time. However, a transient increase in three regions was preceded by a higher proportion of people with short injecting history (≤5 years) and a high prevalence of HCV coinciding with a low prevalence of HIV in the bio-behavioural study. CONCLUSIONS: Bio-behavioural and case-based data were consistent with respect to the regional distribution of HIV and also provided complementary information, with the proportion of new injectors and high HCV prevalence predicting increases in HIV case rates. We identified three regions in Poland that appear to be at increased need for preventive measures. Data point to the need for a stronger investment in harm reduction programmes in Poland. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-015-0828-9) contains supplementary material, which is available to authorized users.